American Spinal Injury Association Impairment Scale Grade E Conversion After Spinal Cord Injury: Incidence, Conversion Characteristics, and Impact of Age on Functional Independence. - Brancato, Gianmarco; Schuld, Christian; Heutehaus, Laura; Jersch, Patrick; Maier, Doris; Freund, Patrick; Pouw, Martin H.; Scivoletto, Giorgio; Weidner, Norbert; Rupp, Ruediger (Topics in Spinal Cord Injury Rehabilitation)
To investigate incidence, conversion, neurological characteristics, and age-dependent functional independence of individuals with initial spinal cord injury (SCI) recovering to American Spinal Injury Association Impairment Scale (AIS) E, meaning normal sensory and motor functions according to the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI). We analyzed 12,221 EMSCI (European Multicenter Study about Spinal Cord Injury) ISNCSCI datasets from 5 time points over the first year after SCI of 4286 individuals (age: 48.7 ± 19 years; 23% female; 92% traumatic, 8% ischemic). Sixty-five of 82 individuals with at least one AIS E exam had an initial assessment within 6 weeks after injury with neurological level of injury peaking at C4 (16.9%) and L2 (15.4%), predominantly AIS grade D (89.2%), and mean total sensory/motor scores reaching 89.4% of their maximum. First AIS E conversion was detected at a median of 171 (interquartile range 274) days after injury. A change point analysis of Spinal Cord Independence Measure (SCIM) III assessments at the time of conversion of 75 AIS E individuals demonstrates a decline of full functional independence with age particularly over 70 years (< 40, 76.9%; 40-70, 42.9%; >70, 14.3%). The current AIS E definition insufficiently reflects the reality experienced by older people without deficits in the ISNCSCI, as functional impairments remain predominantly in mobility-related activities. To detect whether these deficits are related to comorbidities attributable to aging rather than remnant deficits of SCI, functional assessments such as the SCIM should be performed in an age-matched non-SCI control group.